Assaying Hematopoiesis Using Zebrafish - Boatman, Sonja (2013)
The zebrafish has become a commonly used model for studying hematopoiesis as a result of its unique attributes. Zebrafish are highly suitable for large-scale genetic and chemical screens compared to other vertebrate systems. It is now possible to analyze hematopoietic lineages in zebrafish and validate cell function via transplantation assays. Here, we review advancements over the past decade in forward genetic screens, chemical screens, fluorescence-activated cell sorting analysis, and transplantation assays. Integrating these approaches enables new chemical and genetic screens that assay cell function within the hematopoietic system. Studies in zebrafish will continue to contribute and expand our knowledge about hematopoiesis, and develop novel treatments for clinical applications.